2015
DOI: 10.3892/ijo.2015.2924
|View full text |Cite
|
Sign up to set email alerts
|

Sodium valproate, a histone deacetylase inhibitor, modulates the vascular endothelial growth inhibitor-mediated cell death in human osteosarcoma and vascular endothelial cells

Abstract: The level of vascular endothelial growth inhibitor (VEGI) has been reported to be negatively associated with neovascularization in malignant tumors. The soluble form of VEGI is a potent anti-angiogenic factor due to its effects in inhibiting endothelial cell proliferation. This inhibition is mediated by death receptor 3 (DR3), which contains a death domain in its cytoplasmic tail capable of inducing apoptosis that can be subsequently blocked by decoy receptor 3 (DcR3). We investigated the effects of sodium val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 32 publications
(44 reference statements)
2
15
0
Order By: Relevance
“…Previous studies have identified multiple genetic targets affected by HDAC inhibition in various mammalian cell types, including those associated with pluripotency , lineage‐specific differentiation , and cytokine production . In Figure A, quantitative PCR (qPCR)‐based gene expression assays were used to assess the concentration‐dependent effects of NaBu on CMC gene transcription.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have identified multiple genetic targets affected by HDAC inhibition in various mammalian cell types, including those associated with pluripotency , lineage‐specific differentiation , and cytokine production . In Figure A, quantitative PCR (qPCR)‐based gene expression assays were used to assess the concentration‐dependent effects of NaBu on CMC gene transcription.…”
Section: Resultsmentioning
confidence: 99%
“… 10 However, in other studies, VPA was antiangiogenic in models of several cancers. 19 , 20 Thus, the effect of VPA on angiogenesis remains controversial, perhaps attributable to differential regulation of key genes and proteins in various disease microenvironments. The effect of VPA on random skin flap angiogenesis remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…VPA induced the Bcl-2 phosphorylation and release of the cytochrome c via activating ERK1/2 and consequently inhibited the serum starvation-induced HUVECs apoptosis (Michaelis et al, 2006). Comparatively, VPA was found to induce apoptosis of tumor cells (Yamanegi et al, 2015).…”
Section: Hdacs and Endothelial Apoptosismentioning
confidence: 96%